Electromechanical coupling vibration characteristics of an AC servomotor-driven translational flexible manipulator. (15th November 2016) - Ju, Jin-yong; Li, Wei; Yang, Xue-Feng; Wang, Yu-Qiao; Liu, Yu-Fei
The nonstationary transition status of the motor start-up phase creates great threat against the stable operation of the flexible manipulator system. This article investigates the electromechanical coupling dynamics and vibration response characteristics for a flexible manipulator of an alternating current servomotor-driven linear positioning platform with considering the start-up dynamic characteristics of the motor. Based on the constructed global electromechanical coupling effect and the Lagrange–Maxwell equations, the dynamic model of the whole system is established. The electromechanical coupling vibration mechanism of the flexible manipulator is obtained by analyzing the multiphysical process and multiparameter coupling phenomenon of the whole system. The result demonstrates that the nonstationary transition status of the motor initialization phase is mainly manifested during the disturbance of the three-phase stator current. As the speed of the linear positioning platform increases, the current disturbance, arousing the change of the servo driving force of the linear positioning platform, has dominant frequency shift and frequency amplitude decrease. Then, the vibration response of the flexible manipulator is markedly affected and the variation of the high-order modes vibration response is more obvious. The analysis result is significant for improving the dynamic performance of the motor-driven flexible robot manipulator system.